Alternative sewerage system in Malaysia : a new construction technology - Goh, Hong Chun (2004)
Gravity sewer system has been the conventional way of laying sewer pipes and therefore has been the most popular sewer pipe-laying method in the construction industry. However, not all ground conditions favour the gravity sewer system. As such, the main focus of this study is to study one alternative sewerage collection system, which is the vacuum sewerage system, that had been implemented in Malaysia for the past few years. The purpose of this study is to study the characteristics of the Vacuum Sewerage System in terms of the environmental and safety aspects, and aims at identifying the problems faced during the implementation of Vacuum Sewerage System and the main factors contributing to the selection of the Vacuum Sewerage System. A total of 50 questionnaires were distributed to respondents in the state of Kuala Lumpur, Selangor, Johor, Pahang, Perak and Kedah. The feedbacks were analyzed using frequency analysis, average index analysis and relative index analysis. The vacuum sewerage system is a more flexible sewerage system as compared to the conventional gravity system as the construction of vacuum sewerage system in various soil conditions has a lower level of difficulties.